(untitled) (Journal of Partial Differential Equations, 1991)
In this paper we have established the existence of global weak solutions and blow-up properties for the generalized system of ferro-magnetic chain with Gilbert damping term by means of Galerkin method and concavity argument. In addltion, the convergence as &#945 &#8594 0 and &#949 &#8594 0 have also been discussed.